Gender Parity Correction Mechanisms in Open-List Proportional Representation: Evidence from Chile - Perez-Cosgaya, T (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Gender quotas improve women s representation but do not guarantee parity in the composition of political representation bodies. This is more difficult in open-list proportional representation (OLPR) systems. We suggest a good alternative is "parity correction mechanisms" (PCMs), which eliminate elected candidates of the over-represented gender and include unelected candidates of the under-represented gender. Chile introduced two PCMs in the 2021 and 2023 elections. We conclude the following. First, PCMs do not always correct representation in favor of women. Second, PCMs affect the left - and right-wing lists in almost identical proportions. Third, exceptionally, a party loses its seat because of PCM.